1991
DOI: 10.3109/08916939109007650
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Thyroid Peroxidase Antibodies in Thyroid Disorders and Non-Thyroid Autoimmune Diseases

Abstract: A new commercial method for measurement of anti-thyroid peroxidase (anti-TPO DYNOtest, Henning, Berlin) was evaluated in normal subjects and in patients with autoimmune thyroid and non-thyroid diseases, and compared to an immune fluorescence method for measurement of anti-microsomal antibodies (MicAb), and a radioimmunological method for quantifying thyroglobulin antibodies (TgAb). The majority of normal subjects had anti-TPO levels below 52 U/ml and patients with Hashimoto's thyroiditis had levels above 200 U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
4
6

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 13 publications
3
26
4
6
Order By: Relevance
“…Another possibility could be that the lower prevalence of subclinical hypothyroidism in smokers is secondary to the lower prevalence of thyroid autoantibodies. The present study does not directly support this hypothesis as one would expect a stronger association between smoking and TPO-Ab, which has been shown in several studies to correlate better to impaired thyroid function than Tg-Ab (31,37).…”
Section: Gender and Age (Years)contrasting
confidence: 93%
See 1 more Smart Citation
“…Another possibility could be that the lower prevalence of subclinical hypothyroidism in smokers is secondary to the lower prevalence of thyroid autoantibodies. The present study does not directly support this hypothesis as one would expect a stronger association between smoking and TPO-Ab, which has been shown in several studies to correlate better to impaired thyroid function than Tg-Ab (31,37).…”
Section: Gender and Age (Years)contrasting
confidence: 93%
“…The major cause for spontaneous overt hypothyroidism is an autoimmune destruction of the thyroid gland (29). Nearly all patients with newly diagnosed overt hypothyroidism are TPO-Ab-and/or Tg-Ab-positive with TPO-Ab being more common than Tg-Ab (30)(31)(32). Only a modest correlation between the two antibodies has been found and it has been suggested that it is more or less random which antibody is produced (30).…”
Section: Gender and Age (Years)mentioning
confidence: 99%
“…It has been questioned whether Tgab provides further diagnostic information compared with the single use of TPOab (or Micab) in the diagnosis of autoimmune thyroid disease (1,8,23). In our study Tab were with equal frequency directed against Tg and TPO with 14 of 17 of antibody-positive patients having Tgab and 13 of 17 having TPOab.…”
Section: Discussionmentioning
confidence: 91%
“…The Tab detected in previous studies have primarily been against thyroglobulin (Tgab) and microsomal antigens (Micab). It is now possible to measure the more sensitive and antigen-specific anti-thyroid peroxidase antibodies (TPOab) (8,9). However, Tab in serum do not always appear in autoimmune thyroid diseases (10).…”
Section: Introductionmentioning
confidence: 99%
“…An elevated level of antibodies to TPO (TPOab) was reported to be the major risk factor for AITD (16). With sensitive assay techniques, 95% of the patients with hypothyroidism (Hashimoto's thyroiditis) and 85% of those with hyperthyroidism (Graves' disease) have detectable levels of TPOab (17).…”
Section: Introductionmentioning
confidence: 99%